Structural development of 1, 2, 3, 4-tetrahydroisoquinoline-type positive allosteric modulators of prostacyclin receptor (IPPAMs) to improve metabolic stability, and investigation of metabolic fate. Issue 15 (1st August 2017) - Miyachi, Hiroyuki; Suzuki, Toshifumi; Imamura, Riyo; Nagano, Tetsuo; Okabe, Takayoshi
Graphical abstract: Abstract: We synthesized a series of 1, 2, 3, 4-tetrahydroisoquinoline-type positive allosteric modulators of prostacyclin receptor (IPPAMs), aiming to improve the metabolic stability of the previously identified hit compound IPPAM-3 (2 ). Our results indicated that the 3-position of the 2-substituted phenyl ring in this series of IPPAM-3 derivatives is a hot spot for metabolism catalyzed by human hepatic microsomes. This conclusion was confirmed by the finding that8, in which the 3-position is blocked by a fluorine substituent, exhibited superior metabolic stability (t1/2 21 min versus 7 min for parent compound2 ). The primary route of metabolism of8 was found to be oxidative defluorination, i.e., ipso -substitution of the fluorine atom to a hydroxyl group, affording catechol derivative12 . The primary metabolite12 underwent further hydroxylation mainly on the 1, 2, 3, 4-tetrahydroisoquinoline moiety. These findings should be helpful for design of IPPAMs with longer duration of action.